2017
DOI: 10.1139/cjps-2017-0098
|View full text |Cite
|
Sign up to set email alerts
|

Identification and expression analysis of <i>LATERAL ORGAN BOUNDARIES DOMAIN</i> (<i>LBD</i>) transcription factor genes in <i>Fragaria vesca </i>

Abstract: The LATERAL ORGAN BOUNDARIES DOMAIN (LBD) gene family encodes plant-specific transcription factors that play crucial roles in the growth and development in many plant species. However, no systematic study of LBD genes has been conducted in strawberry. In this study, 35 LBD (FvLBD) genes were identified in the diploid woodland strawberry genome (Fragaria vesca). These LBD proteins could be classified into two groups based on the structure of their lateral organ boundaries (LOB) domain. The promoters of FvLBD ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…In previous studies, LBD transcription factors have been identified in many plant species. For example, Malus domestica has 58 LBD genes [20], Fragaria vesca has 35 LBD genes [21], Vitis vinifera has 40 LBD genes [22], Zea mays has 44 LBD genes [23], Morus notabilis has 31 LBD genes [24], Brassica rapa var. rapa has 59 LBD genes [25], and Hordeum vulgare has 24 LBD genes [26].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, LBD transcription factors have been identified in many plant species. For example, Malus domestica has 58 LBD genes [20], Fragaria vesca has 35 LBD genes [21], Vitis vinifera has 40 LBD genes [22], Zea mays has 44 LBD genes [23], Morus notabilis has 31 LBD genes [24], Brassica rapa var. rapa has 59 LBD genes [25], and Hordeum vulgare has 24 LBD genes [26].…”
Section: Introductionmentioning
confidence: 99%
“…The LBD genes are expressed in a band of cells at the adaxial base of all lateral organs formed from the shoot apical meristem and at the base of lateral roots. The LBD genes also regulate plant cell wall thickening and secondary growth ( Chen et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to analyze the relationship between C. sinensis and other plants, the evolution of the LBD TFs in C. sinensis and other plants was studied (Figure 3). Eleven species were included in the analysis: A. thaliana [3], Populus trichocarpa [44], Fragaria vesca [52], M. domestica [4], L. japonicus [42], M. truncatula [42], G. max [9], V. vinifera [10], E. grandis [6], Z. mays [8] and O. sativa [7]. All of the species belong to monocots or eudicots.…”
Section: Evolution Of the Lbd Family Among Plantsmentioning
confidence: 99%